Oral and general health-related quality of life with conventional and implant dentures - Heydecke G, Locker D, Awad MA, Lund JP, Feine JS (Blackwell Synergy, 2003)
Implant overdentures and conventional prostheses have been compared in several trials using a variety of functional and oral health-related quality of life (OHQOL) outcomes.